Correlations between sleep bruxism and temporomandibular disorders - Ohlmann, Brigitte; Waldecker, Moritz; Leckel, Michael; Bömicke, Wolfgang; Behnisch, Rouven; Rammelsberg, Peter (Journal of Clinical Medicine, 2020)
The aim of this study was to identify correlations between sleep bruxism (SB) and temporomandibular disorders (TMD) as diagnosed by means of the research diagnostic criteria for temporomandibular disorders (RDC/TMD). Sleep bruxism was diagnosed on the basis of I) validated questionnaires, II) clinical symptoms, and III) electromyographic/electrocardiographic data. A total of 110 subjects were included in the study. Fifty-eight patients were identified as bruxers and 52 as nonbruxers. A psychosocial assessment was also performed. An RDC/TMD group-I diagnosis (myofascial pain) was made for 10 out of 58 bruxers, whereas none of the nonbruxers received a diagnosis of this type. No significant differences were found between bruxers and nonbruxers with regard to RDC/TMD group-II (disc displacement) and group-III (arthralgia, arthritis, arthrosis) diagnoses. Somatization was significantly more common among bruxers than nonbruxers. Multivariate logistic regression analysis revealed that somatization was the only factor significantly correlated with the diagnosis of myofascial pain. The results of this study indicate a correlation between myofascial pain, as diagnosed using the RDC/TMD, and somatization. It seems that somatization is a stronger predictor of an RDC/TMD diagnosis of myofascial pain than sleep bruxism is.